Central corneal thickness and corneal endothelial characteristics in healthy, cataract, and glaucoma patients - Galgauskas S (Dove Medical Press, 2012)
Saulius Galgauskas, Dalia Krasauskaite, Mykolas Pajaujis, Grazina Juodkaite, Rimvydas-Stanislovas AsoklisVilnius University Faculty of Medicine, ENT and Eye Clinic, Vilnius, LithuaniaPurpose: The aim of this study was to describe and compare endothelial cell parameters and central corneal thickness (CCT) in four different groups of patients (patients with cataract, patients with glaucoma, elderly healthy subjects, and young healthy subjects) and identify correlations between these characteristics, patient age, and sex.Methods: Before conducting invasive procedures, 104 patients were examined using a noncontact specular microscope. Parameters examined included endothelial cell density (ECD), percentage of regular hexagonal cells (6A), average size of endothelial cells (Ave), and CCT). Patients' ages and sexes were also noted.Results: A total of 47 (45%) patients were men and 57 (55%) were women. CCT, ECD, 6A, and Ave in cataract group were 540 (±64) µm, 2633 (±430) cells/mm2, 60 (±10)%, and 390 (±66) µm, respectively; these values in the glaucoma group were 553 (±32) µm, 2484 (±82) cells/mm2, 60 (±10)%, and 397 (±58) µm. In the elderly group these figures were 545 (± 39) µm, 2394 (±416) cells/mm2, 64 (±10)%, and 386 (±43) µm; and in young healthy subjects the values were 555 (±43) µm, 2940 (±345) cells/mm2, 66 (±10)%, and 345 (±42) µm. A weak inverse correlation was observed between ECD and subject age (r = -0.459; P < 0.05) and between ECD and CCT (r = 0.232; P < 0.05). CCT was inversely correlated with patient age (r = -0.13; P = 0.189), but statistically significant data was observed only for the glaucoma group (r = -0.572; P < 0.05).Conclusion: ECD in young subjects was higher than in elderly subjects in all groups; these patients have more endothelial cells and smaller, thicker corneas. The corneal endothelium cells in males have more regular hexagonal cells than do females. No difference in CCT and the ECD was observed between sexes. CCT and average size of endothelial cells do not differ between groups.Keywords: cornea, endothelium, ECD, CCT